Evaluation and analysis of road traffic noise for acoustic comfort in urban public spaces: case study of the Boussouf district, Algeria - Chaour, Soraya; Yousfi, Fahima (Budownictwo i Architektura / Civil and Architectural Engineering, 2026)
In the present work, the sound environment of road traffic was evaluated. The study and analysis of traffic noise were carried out in a part of the Boussouf residential district in Constantine, Algeria. This part contains the main street crossing the heart of the district, through which vehicles pass to enter or leave. The study area was divided into five zones, with 15 measurement points distributed across them. Acoustic indicators such as minimum of sound level Leq,1s (Lmin), maximum of sound level Leq,1s (Lmax), A-weighted sound level exceeded 10% of the time (LA10), A-weighted sound level exceeded 50% of the time (LA50), A-weighted sound level exceeded 90% of the time (LA90), the equivalent sound level over the duration of the measurement, standard indicator in environmental acoustics (LAeq), Traffic Noise Index (TNI), Noise Pollution Level (NPL) and Noise Climate (NC), were recorded and analysed. The studied area exhibits high levels of road traffic noise, exceeding WHO (World Health Organisation) limits and, in some areas, Algerian standards. The NPL and TNI indices indicate a hazard to human health. Thus, acoustic comfort is significantly degraded in nearby recreational areas, and sidewalks as well as adjacent residential buildings are also adversely affected by this noise pollution. Users perceive the space positively if exposure to levels above 65 dB(A) remains brief. The study also shows a general trend in which perceived pleasantness decreases as exposure to higher noise levels increases. However, this relationship is not uniform: it varies significantly depending on the type of space and the associated patterns of use. The interaction between noise exposure and the context of use seems to play a decisive role in shaping perceptions. The findings of this research highlight the importance of considering not only average sound levels, but also their temporal dynamics, when assessing the sound environment.